듀럼밀 유전자원의 질소시비 수준에 따른 농업형질 변이 분석 - 천호선(Hosun Cheon); 곽순화(Sun-Hwa Kwak); 최시은(Sieun Choi); 이수경(Sukyeung Lee); 박진희(Jinhee Park); 김경민(Kyung-Min Kim); 박철수(Chul Soo Park); 모영준(Youngjun Mo) (Korean journal of breeding, 2024)
Breeding wheat cultivars with high nitrogen use efficiency is crucial for sustainableagriculture. In this study, 130 durum wheat accessions from 53 countries were cultivatedunder two nitrogen fertilization levels to investigate variations in agronomic traits andidentify accessions suitable for low-nitrogen conditions. Under no nitrogen fertilization,SPAD value (-99.2), flag leaf length (−15.8 mm), grain area (−0.52 mm2), grain length (−0.27mm), thousand-grain weight (+5.2 g), and grain protein content (−4.2%) showed significantdifferences compared to that under standard nitrogen fertilization. Among thesetraits, the SPAD value exhibited a strong positive correlation with protein content in the absenceof nitrogen fertilization, suggesting its potential as an indicator for selecting germplasmwith superior nitrogen use efficiency. Hierarchical cluster analysis, based on the differencesin the six traits under the two nitrogen fertilization levels, classified the 130 durumwheat accessions into three groups (Groups 1, 2, and 3). Accessions in Group 2 exhibitedsuperior adaptability under no nitrogen fertilization compared with those in the other twogroups. We identified seven accessions in Group 2 that exhibited minimal decreases inSPAD values and protein content under no nitrogen fertilization for use in wheat breedingprograms aimed at developing cultivars with high nitrogen use efficiencies. KCI Citation Count: 0